“It’s complicated” – on communicative relations on the Internet and their determinants (a case study) - Naruszewicz-Duchlińska, Alina (Papers in Linguistics, 2025)
This article analyses the causes, course, and consequences of communicative interactions on the Internet, particularly when verbal exchanges between a content creator and their online audience shift from being neutral and factual to becoming either a verbal conflict or a display of individual and collective support for the creator who perceives themselves as threatened. The point of departure for this discussion is the video “Nie czuję się bezpiecznie na YouTubie” [I don’t feel safe on YouTube] published on November 13, 2023, on the channel “Uwaga! Naukowy bełkot” [Attention! Scientific gibberish] by its founder, scientist, and science communicator Dawid Myśliwiec. The paper explores the dynamics within the triangle of the sender (content creator) – the medium (social media platform) – the audience (commenters) as contextual factors shaping both the creation of the message and its reception. It also identifies and categorizes the types of verbal reactions elicited from the audience.